EDUCAÇÃO DAS RELAÇÕES ÉTNICO-RACIAIS E INFÂNCIA: SEMIFORMAÇÃO E A ATUAÇÃO DOS PROFESSORES - Rogger Diego Miranda (2021)
The approach to ethnic issues caractherizes the theme of this current academic research which objective is to looking to the "Afro-Brazilian History and Culture" impact of practice and analyzing its implications in the Early Childhood Education which refers to the training of teachers for teaching ethnic-racial relations, concerning the inclusion. Stem from semi-formation (Halbbildung), comprehended as part of the reproduction of life under the monopoly of "mass culture" and instrumental reason. On ethnic-racial relations and "Afro-Brazilian Culture and History", the enactment of Law No. 10.639, in 2003, which included in the "Law of Guidelines and Bases for National Education" (LDB) the mandatory teaching of the theme " Afro-Brazilian History and Culture" came up with another possibilities for analysis. In accordance with Jürgen Habermas and the “ethics of discussion” proposed by him, in which moral issues are the object of debate, that an ethical norm is only valid when it is the object of a free dialogue. Methodologically, this research has its documental and analytical structure on ethnic and racial relations.